Analysis of Delay Performance on the Intelligent Fuzzy Logic Dynamic Bandwidth Allocation Algorithm - Radzi N.A.M.; Din N.M.; Al-Mansoori M.H.; Mustafa I.S.; Majid M.S.A. (Springer Verlag, 2023)
The most promising technology in optical data transmission at the access network nowadays is the Ethernet passive optical network (EPON). In this paper, we study the delay performance of an intelligent fuzzy logic based dynamic bandwidth allocation (IFLDBA) algorithm for EPON. We evaluate the performance of EPONs from the simulation perspective, where IFLDBA will be compared with some other well known algorithms in terms of the packet delay and bandwidth utilization. This performance evaluation reveals that the IFLDBA shows significant improvement in terms of the packet delay and bandwidth utilization as compared to other hierarchical dynamic bandwidth allocation algorithms. 2012 King Fahd University of Petroleum and Minerals.